2012
DOI: 10.1155/2012/194839
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation for Treatment of Symptomatic Uterine Fibroids

Abstract: The use of thermal energy-based systems to treat uterine fibroids has resulted in a plethora of devices that are less invasive and potentially as effective in reducing symptoms as traditional options such as myomectomy. Most thermal ablation devices involve hyperthermia (heating of tissue), which entails the conversion of an external electromagnetic or ultrasound waves into intracellular mechanical energy, generating heat. What has emerged from two decades of peer-reviewed research is the concept that hyperthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 53 publications
1
35
0
3
Order By: Relevance
“…Ultrasound-guided RFA can be performed as an outpatient procedure without requiring general anaesthesia and many studies have reported it as a safe and effective treatment for uterine fibroids. [2][3][4][5][6][7][8] However, there are limited data to support ultrasound-guided RFA for adenomyosis which is like uterine fibroids a benign uterine lesion. Therefore, this study was performed to investigate the efficacy and safety of transvaginal ultrasound-guided RFA for the treatment of symptomatic uterine adenomyosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound-guided RFA can be performed as an outpatient procedure without requiring general anaesthesia and many studies have reported it as a safe and effective treatment for uterine fibroids. [2][3][4][5][6][7][8] However, there are limited data to support ultrasound-guided RFA for adenomyosis which is like uterine fibroids a benign uterine lesion. Therefore, this study was performed to investigate the efficacy and safety of transvaginal ultrasound-guided RFA for the treatment of symptomatic uterine adenomyosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, surgical treatment has a relatively high impact on patient lifestyle. In an effort to reduce this impact and decrease other effects (such as the cost of surgical procedures), several less invasive treatment modalities including uterine artery embolisation (UAE), radiofrequency ablation (RFA), and high intensity focused ultrasound (HIFU) ablation have been used in the management of uterine fibroids [4][5][6]. In particular, over the last 10 years, many studies have confirmed that HIFU can be used safely and effectively to treat patients with uterine fibroids; it also has long-term sustained symptom relief, which is associated with the non-perfused volume (NPV) ratio of the fibroids [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…UF are a leading cause of hospitalization for gynecologic disorders (10,11), and they are the primary indication for hysterectomy (12)(13)(14)(15). Hysterectomy is associated with risks (16), and many women would prefer to avoid surgical procedures and opt for medical therapies as an alternate treatment option, if available.…”
mentioning
confidence: 99%